2018
DOI: 10.3389/fimmu.2018.01867
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Novel Role for Fractalkine (CX3CL1) in Memory CD8+ T Cell Accumulation in the Omentum of Obesity-Associated Cancer Patients

Abstract: The omentum is enriched with pro-inflammatory effector memory CD8+ T cells in patients with the obesity-associated malignancy, esophagogastric adenocarcinoma (EAC) and we have identified the chemokine macrophage inflammatory protein-1alpha as a key player in their active migration to this inflamed tissue. More recently, others have established that subsets of memory CD8+ T cells can be classified based on their surface expression of CX3CR1; the specific receptor for the inflammatory chemokine fractalkine. CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 32 publications
7
45
0
1
Order By: Relevance
“…*p ≤ 0.05 responding T cells in this study are also likely due to the redundancy in the chemokine system. Furthermore, it is well reported that many chemokine receptors are internalised upon ligand binding [9,27]. Studies have shown that high levels of chemokines lead to lower levels of their receptors [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…*p ≤ 0.05 responding T cells in this study are also likely due to the redundancy in the chemokine system. Furthermore, it is well reported that many chemokine receptors are internalised upon ligand binding [9,27]. Studies have shown that high levels of chemokines lead to lower levels of their receptors [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that high levels of chemokines lead to lower levels of their receptors [30,31]. This complex process is influenced by the signals in the external microenvironment and the differentiation status of the cell [9]. These dynamic processes were not assessed within the scope of this observational study as the principal aim was to assess the expression pattern of chemokines and their receptors in blood and tissue of these patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractalkine is widely distributed throughout the spinal cord and brain tissue [10]. A pivotal role of activation by fractalkine in inflammation during central nervous system diseases has been well described by previous studies [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Подробно описан механизм этого процесса у больных опухолями пищевода и желудка, связанными с ожирением [45]. Основную роль в их миграции из крови в сальник играет фракталкин -хемокин, вырабатывающийся многими клетками, в том числе адипоцитами [46].…”
Section: влияние адипоцитов сальника на иммунокомпетентные и опухолевunclassified